SUPPLY CHAIN ANALYSIS, INVENTORY CONTROL, AND INFORMATION SYSTEM DESIGN FOR FRESH FRUIT RETAIL MSMEs - Atik Febriani; Muhammad Rizki Pambudi; Rui Almer Guritno; Kuntoro Bayu Pringgondani; Muhammad Vicky Maulana (Universitas Islam Nahdlatul Ulama Jepara, 2026)
This study aims to formulate inventory-control policies and a simple information-system design for a fresh-fruit retail micro, small, and medium enterprise by using supply-chain mapping and retail activities as the operational diagnostic basis. A case study was conducted at Krisbi Buah Purwokerto through observation, interviews, supply-chain and value-chain mapping, supplier-relationship analysis, safety-stock and reorder-point calculations, and an as-is/to-be information-system gap analysis. Four products were purposively selected to represent differences in sourcing origin, chain length, demand rate, and shelf life. The results show that apples have the longest supply chain through import and distributor routes, whereas mangoes have a shorter chain but higher seasonal dependence. Procurement, inventory recording, sales, and reporting remain fragmented, preventing demand information from consistently supporting purchasing decisions. Mango is the principal fast-moving product, with estimated demand of 28.6 kg/day. Using a 95% service-level target, a daily demand standard deviation of 5 kg, and a two-day lead time, the recommended safety stock is 12 kg and the reorder point is 70 kg. The proposed Google Sheets prototype comprises six connected modules covering suppliers, procurement, inventory, sales, dashboards, and monthly reports. The study contributes an integrated link between supply-chain characteristics, inventory policies, and low-cost information-system requirements for micro-retailers. The design remains conceptual and requires user testing and post-implementation performance evaluation.